2011
DOI: 10.1057/crr.2011.22
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Corporate Social Responsibility and Profitability: The Case of Royal Dutch Shell Plc

Abstract: The field of corporate social responsibility (CSR) has grown exponentially in the last decade. Nevertheless, there remains a protracted debate about the legitimacy and value of corporate responses to CSR concerns. This study explored whether CSR is linked to profitability. This study bases its measurement of CSR on content analysis of the annual reports of Royal Dutch Shell Plc. This research used a case study approach and analysed data from several key performance indicators reported in Royal Dutch Shell Plc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 20 publications
3
32
0
8
Order By: Relevance
“…This would be achieved by using the trend line analysis to get the linear correlation coefficient (R-square). This method of analysis is consistent with the work of other researchers [12] and [8].…”
Section: Methods Of Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…This would be achieved by using the trend line analysis to get the linear correlation coefficient (R-square). This method of analysis is consistent with the work of other researchers [12] and [8].…”
Section: Methods Of Analysissupporting
confidence: 90%
“…This study bases its measurement of CSR on content analysis of the annual reports of Dangote Cement Plc. This method is similar to that used by [12] and [8] …”
Section: Methodsmentioning
confidence: 99%
“…Ekatah, Samy, Bampton, and Halabi () sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression. Their results indicate a possible positive relationship, where socially responsible firms are more profitable than their counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wagner () used social indices developed by Waddock and Graves, Ekatah et al () developed key performance indicators for social performance, Sariannidis et al () used nonfarm payroll employment as a social indicator, Ferrero‐Ferrero et al () analyzed the ESG performance of companies, and Beck et al () used Vigeo‐Eiris for CSR and sustainability ratings.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…It indicated that CSR is positively related to better financial performance and this relationship is statistically significant, supporting, therefore, the view that socially responsible corporate performance can be associated with a series of bottom-line benefits. Ekatah, Samy, Bampton, and Halabi (2011) concluded that the findings indicate that CSR is positively related to better financial performance (profitability) and this relationship is statistically significant. Lyon (2007) said that profitability is the most important aspect affecting a firm's growth and survival and it can be seen from the positive relationship between CSR and profitability.…”
Section: Development Of Hypothesesmentioning
confidence: 95%